Perkembangan Perbankan Syariah di Indonesia - Y, Yudi; N, Nurnasrina; Bte Salman, Nola Fibriyani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study examines the development of Islamic banking in Indonesia, starting with the establishment of Bank Muamalat in 1991 as the first Islamic bank. This sector offers financial products and services that comply with Islamic principles, attracting the interest of those seeking interest-free alternatives. Regulatory support from the government, through policies from Bank Indonesia and the Financial Services Authority (OJK), along with socialization programs, has strengthened the growth of Islamic banking. Although it still holds a small market share, increasing public awareness and the adoption of digital technology present greater growth opportunities. In the future, Islamic banking is expected to make a more significant contribution to the national economy and support better financial inclusion in Indonesia.